Estimating walking demand at transit stations - Soh, Kayda Xin Yi. (2012)
With a current population of 5 million and an average population density of 7126 per square kilometre, Singapore is fast becoming one of the most densely populated countries in the world. While population growth would bring about economic growth and diversity, it also has its challenges namely, building a sustainable transport system for the ever-increasing population. With the number of commuters rising exponentially, it is imperative to build a transport network that will enable the commuters to travel to their destinations with ease and efficiency.